A evolução de estudos neurocientíficos & linguísticos sobre habilidades linguísticas. The evolution of neuroscientific & linguistic studies about linguistic abilities - Flôres, Onici Claro (2020)
This article relates the evolution of neuroscientific and linguistic studies on linguistic skills: speaking, (listening), reading and writing, while highlighting that neuroscientific investigations have mapped, still in the 19th century, two brain areas of language - Broca and Wernicke - based on research on speech disorders (aphasias). As for linguistics, it officially began in the XX century, with Saussure, who prioritized speech (langue). The following linguistic skill researched by neurosciences, already in the 20th century, was reading and its difficulties (dyslexia) through the theory of reading routes (Coltheart, 1978; Coltheart, Patterson, Marshall, 1980). In addition, Dehaene (2007) mapped the brain base of the reading activity, already in the XXI century. It should also be noted that the current interest in the study of reading by teachers from different academic disciplines, linguists, psycholinguists and researchers from the most different areas, is due to the great difficulties of reading and comprehension expressed by students of all degrees of education in Brazil. With regard to writing, even today there are few studies in neurosciences and even less in linguistics. Finally, it is added that it is essential to be very careful regarding the attribution of the diagnosis of developmental dyslexia (DD) to children, because there is still not a final scientific response related to the cause of this disorder.